Optimizing the STAD Model in Basic Geometry Learning in Grade V: A Case Study on the Area of Trapezoids and Kites - Ageng Triyono; Rusmin R. M. Saleh; Rintis Rizkia Pangestika; Teguh Wibowo; Dyan Murdiasih (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to examine the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in improving basic geometry learning outcomes among fifth-grade elementary students, specifically on the topic of the area of trapezoids and kites. The research employed a Classroom Action Research (CAR) design based on the Kemmis and Taggart spiral model, conducted over two cycles involving 29 students with heterogeneous backgrounds. Each cycle consisted of planning, implementation, observation, and reflection phases. Data were collected through learning outcome tests, observations of student activities and teacher performance, questionnaires, and interviews. The results showed an increase in average scores from 58.34 (pre-action) to 61.96 (cycle I) and 76.03 (cycle II). The percentage of mastery learning improved from 48.28% to 100%. Student activity, motivation, and group engagement also increased significantly. These findings affirm that the STAD model is effective in enhancing conceptual understanding and learning outcomes in geometry, while also fostering a collaborative and enjoyable classroom atmosphere. It is recommended to implement the STAD model more broadly and to explore the use of innovative learning media in future research.